Liraglutide in Children and Adolescents with Type 2 Diabetes - (:unkn) unknown (MASSACHUSETTS MEDICAL SOC, 2019)
This trial assessed the efficacy and safety of liraglutide as compared with placebo, added to metformin (with or without basal insulin treatment), in children and adolescents with type 2 diabetes. The addition of liraglutide was efficacious and relatively safe in improving glycemic control over 52 weeks. Background Metformin is the regulatory-approved treatment of choice for most youth with type 2 diabetes early in the disease. However, early loss of glycemic control has been observed with metformin monotherapy. Whether liraglutide added to metformin (with or without basal insulin treatment) is safe and effective in youth with type 2 diabetes is unknown. Methods Patients who were 10 to less than 17 years of age were randomly assigned, in a 1:1 ratio, to receive subcutaneous liraglutide (up to 1.8 mg per day) or placebo for a 26-week double-blind period, followed by a 26-week open-label extension period. Inclusion criteria were a body-mass index greater than the 85th percentile and a glycated hemoglobin level between 7.0 and 11.0% if the patients were being treated with diet and exercise alone or between 6.5 and 11.0% if they were being treated with metformin (with or without insulin). All the patients received metformin during the trial. The primary end point was the change from baseline in the glycated hemoglobin level after 26 weeks. Secondary end points included the change in fasting plasma glucose level. Safety was assessed throughout the course of the trial. Results Of 135 patients who underwent randomization, 134 received at least one dose of liraglutide (66 patients) or placebo (68 patients). Demographic characteristics were similar in the two groups (mean age, 14.6 years). At the 26-week analysis of the primary efficacy end point, the mean glycated hemoglobin level had decreased by 0.64 percentage points with liraglutide and increased by 0.42 percentage points with placebo, for an estimated treatment difference of -1.06 percentage points (P<0.001); the difference increased to -1.30 percentage points by 52 weeks. The fasting plasma glucose level had decreased at both time points in the liraglutide group but had increased in the placebo group. The number of patients who reported adverse events was similar in the two groups (56 [84.8%] with liraglutide and 55 [80.9%] with placebo), but the overall rates of adverse events and gastrointestinal adverse events were higher with liraglutide. Conclusions In children and adolescents with type 2 diabetes, liraglutide, at a dose of up to 1.8 mg per day (added to metformin, with or without basal insulin), was efficacious in improving glycemic control over 52 weeks. This efficacy came at the cost of an increased frequency of gastrointestinal adverse events. (Funded by Novo Nordisk; Ellipse ClinicalTrials.gov number, .)
Keywords: PHARMACOKINETICS; METFORMIN; PLACEBO; SAFETY; YOUTH